Tourism Planning: Hospitality and Cultural Identity in the Squares, Parks, Museums, and Fountains of São Borja in the Jesuit Missions Region of Rio Grande do Sul (Interdisciplinary Studies Journal, 2021)
The objective of this study is to present the cultural identity evidenced in the squares, parks, museums, and water fountains of São Borja, elements that contribute to the development of the tourist offerings shaped by the history and material and intangible cultural heritage, natural resources, and investments in local infrastructure. Tourism planning is the responsibility of the public administration, which, together with the private sector, contributes through investments that enhance the tourist offerings. The combination of these factors has the potential to develop the location and justifies new investments, which in turn promote the development of local and regional tourism. Bibliographic research and data collection through fieldwork allowed the identification of the cultural identity represented in São Borja's squares, parks, museums, and fountains, also enabling the identification of elements that contribute to shaping its cultural identity, making tourism a means capable of fostering social, cultural, and economic development.
Keywords: Hospitality; Cultural Heritage; Planning; Tourism